Hybrid model of the plasma accelerator with open walls and closed electron drift - Litovko, I.; Goncharov, A.; Dobrovolsky, A.; Najko, I.; Najko, L. (Вопросы атомной науки и техники, 2018)
The original approach to use Hall-type plasma accelerators with closed electron drift and open walls for production converging towards axis accelerating ion beam describes here. The two-dimensional theoretical hybrid model was created. The performed computer modeling showed that in high-current mode the potential drop forms at the axis. This effect can be used for self consistent accelerating the ions moving toward the system center and then along the axis in both directions.